The Role Of Tourism And Culture Department In The Development Of Bandengan Beach Tourist Area In Jepara Regency - Bima, Bima (Unnes Political Science Journal, 2018)
Tourism development is directed in the role of social and economic activities, to create jobs, to increase community's incomes, as well as local revenues. The development of facilities and infrastructure as a support in the development of tourism destinations need to be balanced with the empowerment of local people around the tourist area. Therefore, the development of tourist areas is needed. The purpose of this study is to know the role, socio-economic impact and constraints of Tourism and Culture Department in the development of Bandengan Beach tourist area. The research method is qualitative. The focus of the research is the role, socio-economic impact and constraints of the Tourism and Culture Department in the development of Bandengan Beach tourist area. Source of data wereobtained from interviews, documentation, and observation. Data validity was tested by triangulation technique. Data were analyzed interactively through the steps of data collection, data reduction, data presentation, conclusion, and verification. The Hierarchy Process Analysis Method of determining priority development of tourist areas used with the application of expert choice. The research results show that the role of Tourism and Culture Department in the development of Bandengan beach tourist area by means of human resource development, tourism product development, market development and marketing, also institutional development. Socio-economic impacts on people's lives. Social impacts include people's mindset, community behavior and self-confidence. The impact of the economic changes experienced is the increase in income. The constraints experienced by the Department of Tourism and Culture in the development of Bandengan beach tourist area are internal and external constraints. This internal obstacle are the limited budget and still lack expertise while external constraint comes from low level of public awareness.